Marfan syndrome: Case series from a single family - Bastola, P (Nepal Journal of Medical Sciences, 2012)
Marfan syndrome is an inherited connective-tissue disorder transmitted as an autosomal dominant trait. It is noteworthy for its worldwide distribution, relatively high prevalence, clinical variability, and pleiotropic manifestations. We describe here cases of Marfan syndrome accidentally found from a remote area of western hilly part of Nepal in three children out of eight children of same family. These cases came to attention in an Ophthalmologic diagnosis, screening and treatment camp. With suspicion of having some ocular problem, patients were brought to the hospital and a diagnosis of Marfan syndrome was made. All the children had similar ocular problem, which was diminution of vision, subluxated lens, myopia, increased length of the eye, one of the children had large looking eye ball, of which the patient and family members were unaware of. Family history revealed early demise of the mother at the age of forty two years. DOI: http://dx.doi.org/10.3126/njms.v1i2.6614 Nepal Journal of Medical Sciences. 2012;1(2): 132-4